2018
DOI: 10.2147/ccid.s164848
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of incobotulinumtoxinA in the management of the masseter using two different injection techniques

Abstract: BackgroundIncobotulinumtoxinA (Xeomin Cosmetic®) has been used previously in the management of masseteric hypertrophy. However, a standardized injection technique has not been established. The goal of the present study was to evaluate the efficacy and safety of two injection techniques in the management of masseteric hypertrophy using incobotulinumtoxinA.MethodsThirty female patients with masseteric hypertrophy were recruited and evenly randomized to receive bilateral treatments of either a single-injection te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 15 publications
(10 reference statements)
1
25
0
Order By: Relevance
“…The longevity of the results of our study was shown to expand into the 36th week postinjection. This was in sync with the study by Andrean et al study where the improvement with incobotulinumtoxinA was found better from 16 to 20 weeks for two sessions in Caucasian population 10 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The longevity of the results of our study was shown to expand into the 36th week postinjection. This was in sync with the study by Andrean et al study where the improvement with incobotulinumtoxinA was found better from 16 to 20 weeks for two sessions in Caucasian population 10 …”
Section: Discussionsupporting
confidence: 90%
“…Shome et al 4 have already published a 4‐year follow‐up paper that demonstrated long‐term use of onabotulinumtoxinA for the hypertrophied masseter muscle, subsequently narrowing the width of the lower half of the face. Also, there are few short‐term studies on incobotulinumtoxinA comparing the results of single‐injection technique and multiple‐injection techniques for reducing the masseter muscle hypertrophy 10 . Past studies by Shome et al 7 highlighting the diffusion characteristics of incobotulinumtoxinA mentioned that the propensity of side effects may be higher with incobotulinumtoxinA as compared to onabotulinumtoxinA owing to the dispersion properties of incobotulinumtoxinA.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were as follows: current pregnancy or lactation, hypersensitivity or allergy to incobotulinumtoxin type A, known disorders of normal muscle contractility (eg, myasthenia gravis or Lambert-Eaton Syndrome), presence of infection at the site of injection (ie, mandibular angle), inability to comply with follow-up examinations, abstain from facial procedures during the 6-month follow-up period of the study and having a score of ≥2 on the Merz Aesthetics Scale for jowling. 7 A detailed description of the inclusion/exclusion criteria of the screened sample has been published previously. 7 This study received approval from the independent review board "Veritas IRB" and can be tracked at: www.clini caltr ials.gov (Identification-number: NCT03376464).…”
Section: Study Samplementioning
confidence: 99%
“…7 A detailed description of the inclusion/exclusion criteria of the screened sample has been published previously. 7 This study received approval from the independent review board "Veritas IRB" and can be tracked at: www.clini caltr ials.gov (Identification-number: NCT03376464). The procedures were performed in adherence to the Declaration of Helsinki (1996), in accordance with regional laws and good clinical practice for studies in human subjects.…”
Section: Study Samplementioning
confidence: 99%
“…This subsequently causes paralysis and atrophy of the muscle. In the case of masseter muscle hypertrophy, single injection technique involving the delivery of 40 U of incobotulinumtoxin A is considered to be both safe and effective (4). The technique of a successful botulinum injection depends on accurate localisation of the motor point of masseteric muscle.…”
Section: Introductionmentioning
confidence: 99%